Complete childhood vaccination and associated factors among children aged 12-23 months in Dabat demographic and health survey site, Ethiopia, 2022 - Abebaw Addis Gelagay; Abebaw Gebeyehu Worku; Debrework Tesgera Bashah; Nigusie Birhan Tebeje; Mignote Hailu Gebrie; Hedija Yenus Yeshita; Endeshaw Adimasu Cherkose; Birhanu Abera Ayana; Ayenew Molla Lakew; Desalegn Anmut Bitew; Desale Bihonegn Asmamaw; Wubshet Debebe Negash; et al. (BMC, 2023)
Abstract Introduction Childhood immunization is one of the most cost-effective public health strategies to prevent children's mortality and morbidity from infectious diseases, but the Covid-19 pandemic and associated disruptions have strained health systems, and worldwide 25 million children missing out on vaccination in 2021. Of the 25 million, more than 60% of these children live in 10 countries including Ethiopia. Therefore, this study aimed to assess complete childhood vaccination coverage and associated factors in the Dabat district. Method A community-based cross-sectional study was conducted from December 10/2020 to January 10/2021Gregorian Calendar. The data for this study was extracted from information collected for the assessment of maternal, Neonatal, and Child Health and health services utilization in the Dabat demographic and health survey site. Vaccine-related data were collected using an interviewer-administered questionnaire. An adjusted odds ratio with a 95% confidence interval was used to identify the presence and the direction of the association. Results Based on vaccination cards and mothers/caretakers' recall 30.9% (95%CI: 27.9-34.1%) of children aged 12-23 months in the Dabat district were completely immunized. Urban residency [AOR 1.813, 95% CI: (1.143, 2.878)], delivered in the health facility [AOR = 5.925, 95% CI: (3.680, 9.540)], ANC follow-up during their pregnancy [AOR 2.023, 95% CI: (1.352, 3.027)], rich wealth index [AOR = 2.392, 95% CI: (1.296, 4.415)], and parity [AOR 2.737, 95% CI: (1.664, 4.500)] were significantly associated with complete child vaccination. Recommendation and conclusion Complete vaccination coverage among children aged 12-23 months in the Dabat district was lower than the Global vaccine plan and Ethiopian ministry of health goal in 2020. Therefore, Health care providers and other stakeholders should mobilize the community to improve mothers' health-seeking behavior toward pregnancy follow-up and health facility delivery to improve childhood vaccination. Besides, expanding the service to remote areas are necessary to increase the immunization access.